Meditation in the third-person perspective modulates minimal self and heartbeat-evoked potentials - Hang Yang; Bruno Herbelin; Chuong Ngo; Loup Vuarnesson; Olaf Blanke (NeuroImage)
Experienced meditation practitioners often report altered states of their sense of self, including decentering and distancing the self from the body and one’s current concerns. Altered states of the sense of self, such as disembodiment and distancing of the self from the body, have also been induced experimentally using virtual reality (VR) and linked neurally to heartbeat-evoked potentials (HEPs). Whereas studies investigated the related neural correlates of such decentering during meditation, none experimentally modulated the sense of self during meditation practice using VR nor determined the potentially associated behavioral changes of the sense of self. Here we determined HEPs and behavioral measures in 23 participants who performed a guided meditation in VR, either from a third-person (3PP) or first-person perspective (1PP) to modulate the sense of self. In the 3PP-vs-1PP meditation condition, we report immediate effects including stronger sensations of detachment and disconnection, reduced salience of the perceived body boundary, and reduced self-identification with the body. HEP analysis revealed a more negative HEP amplitude in the 3PP condition, associated with activation of the posterior cingulate cortex and medial prefrontal cortex. Leveraging a new VR-supported meditation platform and methods, these data link the sense of self in meditation practice to the neuroscience of the bodily self, based on short-term subjective, behavioral, and neural changes. The study provides a foundation for future research on whether manipulating the minimal self in VR can aid in cultivating self-transcendent experiences reported by experienced meditators and whether integrating this manipulation facilitates the cultivation of long-term changes.